Автор:
arnaldomurphy4tg^2x-2tgx-3tg^2x-3=0
tg^2x-2tgx-3=0
Пусть tgx=y, получим y^2-2y-3=0
D=(-2)^2-4*1*(-3)=16
y1=(2+4)/2=3, следовательно tgx=3⇒ x= arctg3+πn, n∈Z
y2=(2-4)/2=-1, следовательно tgx=-1⇒x=arctg(-1)+πn, n∈Z⇒ x=-π/4+πn, n∈Z
Ответ: x= arctg3+πn, n∈Z; x=-π/4+πn, n∈Z
Автор:
dudleyschwartzДобавить свой ответ
Предмет:
МатематикаАвтор:
gingersnapОтветов:
Смотреть
Предмет:
ГеографияАвтор:
brianaixsgОтветов:
Смотреть
Предмет:
Русский языкАвтор:
baby carrotovnlОтветов:
Смотреть
Предмет:
Русский языкАвтор:
tuesdayОтветов:
Смотреть